The Effect of E-Commerce on Product Selling Power to MSMEs Moslem Owners - Ahmad Fadlan; Mohammad Yusuf; Herurel Pernanda (Proceeding International Conference on Religion, Science and Education, 2023)
This study aimed to analyze the effect of e-commerce on product selling power. It was studied on products which were produced by Micro, Small and Medium Enterprises (MSMEs) that were owned by Moslem owners at Klambir V Kebun village, North Sumatra. Most of products were cullinary. A descriptive quantitative method through a questionnaire was used as data collection. The questionnaire was distributed to thirteen MSMEs Moslem owners and then were analyzed by using SPSS 22.0. The result findings revealed that there was a significant linear relationship between X variable and Y variable, which meant that e-commerce affected product selling power to MSMEs Moslem Owners at Klambir V Kebun village, North Sumatra. It was also found that 86.9% e-commerce influenced product selling power, while the remaining 13.1% was influenced by other variables which were not analyzed in this study.